Recreational Cannabis Use Before and After Legalization in Women With Pelvic Pain. Issue 1 (January 2021) - Geoffrion, Roxana; Yang, Emily C.; Koenig, Nicole A.; Brotto, Lori A.; Barr, Alasdair M.; Lee, Terry; Allaire, Catherine; Bedaiwy, Mohamed A.; Yong, Paul J.
Abstract : OBJECTIVE: To evaluate the prevalence and characteristics of recreational cannabis use in women with pelvic pain, and to examine the influence of cannabis legalization on these parameters. METHODS: We conducted a retrospective analysis of a prospective registry of women with self-reported moderate-to-severe pelvic pain referred to a tertiary care clinic in Vancouver, Canada, 2013–2019. We excluded patients aged 18 years or younger and those with unknown data on cannabis use. Demographic, clinical, and validated questionnaire data were extracted for two main analyses: 1) comparison of current cannabis users with current nonusers, and 2) comparison of current cannabis users who entered the registry before cannabis legalization (October 17, 2018) with those who entered the registry on or after legalization. RESULTS: Overall, 14.9% (509/3, 426) of patients were classified as current cannabis users. Compared with nonusers, cannabis users were younger ( P <.001), had lower levels of education ( P <.001) and lower household income ( P <.001), were taking opioids ( P <.001), antiinflammatories ( P =.003), neuromodulators ( P =.020), and herbal medications ( P <.001) more frequently. They had worse questionnaire scores for depression, anxiety, pain catastrophizing, quality of life, and pelvic pain severity ( P <.001 for all). After cannabis legalization, prevalence of current cannabis use increased from 13.3% (366/2, 760) to 21.5% (143/666) ( P <.001). Compared with prelegalization, postlegalization users were associated with higher levels of education ( P <.001), worse anxiety ( P =.036), and worse pain catastrophizing ( P <.001) scores. They were taking fewer antiinflammatories ( P <.001), neuroleptics ( P =.027) and daily opioids or narcotics ( P =.026), but more herbal medications ( P =.010). CONCLUSION: Recreational cannabis use increased among patients with pelvic pain after legalization in Canada. Cannabis users had worse pain-related morbidities. Postlegalization, cannabis users were less likely to require daily opioids compared with cannabis users before legalization. The role, perceived benefits, and possible risks of cannabis for pelvic pain require further investigation. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT02911090. Abstract : Recreational cannabis use significantly increased among patients with pelvic pain after legalization in Canada, and cannabis users had worse pain-related morbidities compared with nonusers.